Realitas Penggunaan Bahasa Indonesia dalam Media Sosial TikTok Mahasiswa - Dewani, Shinta Laura; Presida, Sesy Briliana; Saputra, Agung Faizs; Putri, Cahya Soviyah (Indonesian Journal Publisher, 2024)
This study aimed to investigate how the TikTok social media platform influences the development of Indonesian language among students, the role of TikTok in shaping language subcultures in campus communities, and the potential negative impacts of students' language use on TikTok. The study used a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and open-ended questionnaires. The results of the study showed that TikTok can be a positive force for language development, as it can encourage creativity, self-expression, and the use of new terms and phrases. However, TikTok can also have negative impacts, such as the use of offensive language, the loss of linguistic authenticity, and the creation of a poor digital footprint.